Housing First and the Reassembling of Permanent Supportive Housing: The Limits and Opportunities of Private Rental. Issue 1 (2nd January 2018) - Parkinson, Sharon; Parsell, Cameron
Abstract: Third sector agencies have played a central role in the social innovation of permanent supportive housing following deinstitutionalization and the emergence of a choice-based regime. This paper traces the reassembling and translation of permanent supportive housing that gained particular saliency through the globalised Housing First movement and the reassembling of private rental as a form of permanent supportive housing. Drawing on the concept of transformative social practices informed by resilience and assemblage thinking, we add new insights to existing literature by re-examining why agencies and models followed divergent paths and the resulting implications this has had in the quest to end homelessness. We argue that the failure to effectively implement such models according to a narrowly defined prescription of Housing First does not just stem from a lack of affordable housing but must be understood in the historically contested space of how affordable housing and support should be provided that is translated through the market, state and civil society relations assembled across time and place. Drawing on cases from Belgium, United States and Australia, it is concluded that evolutionary resilient social innovation in private rental PSH necessitate increased and ongoing engagement rather than a retreat of the State.